Pirates of the Caribbean : dead man's chest - Bader, Diedrich, 1966-; Kryczko, Ted.; Thornton, Randy; Bazuldua, Barbara; Disney Enterprises (1996- ) (New York, N.Y. : Disney Press, 2007)
"Read along as Captain Jack Sparrow, Will Turner, and Elizabeth Swann face new dangers. Voices and sound effects straight from the film bring the adventure to life."--Cover back.
"Storybook and CD"--P. [1] of cover]
"With original movie voices and sound effects"--P. [1] of cover.
Sound disc producers Ted Kryczko and Randy Thornton; co-producer/engineers, Jeff Sheridan and Dan Montes; adapted by Barbara Bazuldua, Randy Thornton and Ted Kryczko; design by Steve Sterling.
Diedrich Bader, narrator; Johnny Depp, San Shella, Kevin R. McNally, Stellan Skarsgard, Tom Hollander, Orlando Bloom, Keira Knightley, Naomie Harris, Bill Nighy, Dermot Keaney, Jack Davenport, cast.
Juvenile
Keywords: Pirates -- Fiction; Buried treasure -- Fiction; Caribbean Sea -- Fiction